THE ISLAMIC EDUCATION WITHOUT DISCRIMINATION IN THE QUR'AN PERSPECTIVE - Basri, Basri (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2022)
Discrimination in education often occurs in people's lives. This discrimination arises because of the blurring of public awareness about the multi-ethnic and multi-religious plurality that grows in a diverse society. Discriminatory practices can occur due to religious interests, ethnic differences, economic aspects, and health dimensions. This article uses literature research and a qualitative approach and analyzes with a descriptive study of verses that teach values ​​without discrimination. The verses used are Surah Al-Hujurat [49]: 13, Abasa [80]: 1-11, and Al-Maidah [5]: 8. The results of the study conclude two namely; First, Islamic education teaches anti-discriminatory values ​​in various aspects, especially in ​​education. Education in Islam should not prioritize individuals or groups based on material and ethnicity. Second, discriminatory attitudes reflect someone's heart that cannot balance justice and interests. Inclusive education will be present in society if an open attitude, willingness to get to know each other, and respect for differences by not discriminating against certain groups have grown in every Muslim.